Cultural conformity and persistence in Dickcissel song are higher in locations in which males show high site fidelity. Issue 1 (4th October 2021) - Parker, Timothy H; Sousa, Bridget; Leu, Stephan T; Edmondson, Stacy; Foo, Cecily; Strauss, Amy; Kahl, Hanna; Ballinger, Kristen; Ross, Eric; Große Ruse, Mareile; Sandsten, Maria; Verheijen, Bram H F; et al.
Abstract: Dickcissel ( Spiza americana ) males occupying territories in cropland sites produced songs that were less similar on average to other Dickcissel songs in their neighborhood than did Dickcissels living in grasslands, where conformity to the local vocal culture was higher. Further, Dickcissel vocal culture changed more quickly over time in cropland sites relative to grassland sites. These differences may have resulted from the lower site fidelity we observed in Dickcissel males in cropland sites relative to grassland sites. We expected this link with site fidelity because we hypothesized that conformity to local culture in Oscine songbirds and the persistence of culture over time and space are promoted by habitats that facilitate stable populations. In contrast, sites in which habitat features cause rapid population turnover provide more territory vacancies and so more opportunities for colonization. Colonization should drive cultural change, either through adult colonists importing foreign cultural variants or young colonists making errors as they learn the local song. This potential link between population turnover and cultural stability may apply to animal cultures more broadly and so may be a fruitful area for further research. Besides the link between site fidelity and cultural change over time, we also investigated the possibility that habitats with different levels of site fidelity might show differences in the spatial scale of song similarity. However, we found no evidence of such a difference. Finally, although our conclusions regarding conformity and change in vocal culture were based on many recorded songs, automated assessments of song similarity imprecisely estimated the overall degree of song similarity. Thus, we may have underestimated the strength of the effects of time and distance on song similarity. Lay Summary: Most songbirds learn their complex vocalizations from each other. When birds learn song from their neighbors, this often leads to differences in songs within the same species from place to place; in other words, geographic cultural differences, sometimes referred to as dialects. We are interested in how these song cultures change over time and across the landscape, and we hypothesized that the persistence of song culture might be influenced by the rate of turnover of individual birds (driven by death, emigration, and immigration). In the Dickcissel ( Spiza americana ), a grassland songbird, we found higher rates of population turnover in croplands than in grasslands, and consistent with our hypothesis, evidence that song culture changed more quickly in croplands than in grasslands. We hope this result will spur more research into the relationship between population turnover and cultural change in a wider variety of species and contexts to assess the generality of this finding.